Global Instability: The Political Economy of World Economic Governance. - Grieve-Smith, J (Routledge, 1999)
Authors examine the problems of the world economy in the era of globalisation and outline possible solutions. They challenge the belief that the new globalised economy resists any change of course. The book reviews international economic institutions, the linked crises which recently hit Asian economies, the implications of globalisation, the role of multinational investment, the IMF and the World Bank.